Evaluation of the Productivity and Impact of International Taxation Research: A Bibliometric Review - Judijanto, Loso (West Science Accounting and Finance, 2024)
This research method paper proposes a comprehensive framework for evaluating the productivity and impact of international taxation research through bibliometric analysis. As the field of international taxation continues to evolve rapidly, understanding the landscape of research productivity and impact becomes imperative for policymakers, scholars, and practitioners. Bibliometric analysis offers a systematic approach to assess the scholarly output, citation patterns, and influence of research in this domain. This paper outlines the steps involved in conducting a bibliometric analysis, including data collection, bibliographic database selection, citation analysis, and visualization techniques. Additionally, it discusses potential challenges and limitations in bibliometric analysis and suggests strategies for mitigating these issues. By employing this methodological framework, researchers can gain valuable insights into the trends, gaps, and contributions within the field of international taxation, ultimately facilitating evidence-based decision-making and advancing scholarly discourse.